Lack of electron microscopy hinders correct renal biopsy diagnosis: A study from India. (2nd January 2016) - Kurien, Anila Abraham; Larsen, Christopher; Rajapurkar, Mohan; Bonsib, Stephen M.; Walker, Patrick
ABSTRACT: Electron microscopy (EM) is performed routinely on all native kidney biopsies in the western world. However, in India, it is not regularly performed due to non-availability and financial constraints. The aim of this prospective study was to evaluate the usefulness of routinely performing EM on native kidney biopsies. In order to eliminate selection bias, all consecutive native kidney biopsies were included in this study, provided they had adequate tissue for light, immunofluorescence (IF), and EM. The biopsies were reported on the basis of light and IF microscopy. EM was performed on each case by another pathologist who also independently reviewed the light microscopic slides and IF images. The findings were then reviewed to assess how the ultrastructural features contributed to the primary diagnosis and assigned to one of the following categories: 1. Crucial for diagnosis, 2. Important contribution, or 3. Not required. Of the 115 cases evaluated, EM was crucial in 12% of the cases. In 20% of the cases, it provided important confirmatory information and in the remaining 68% cases, EM was not considered required. This study supports the use of EM as a routine diagnostic tool in the evaluation of native kidney biopsies. There is an urgent need for availability and accessibility of EM in our country.